Quality of life in elderly patients with localized breast cancer treated with radiotherapy. A prospective study. (April 2016) - Arraras, Juan Ignacio; Manterola, Ana; Asin, Gemma; Illarramendi, Jose Juan; Cruz, Susana de la; Ibañez, Berta; Delfrade, Josu; Salgado, Esteban; Zarandona, Uxue; Cambra, Koldo; Vera, Ruth; Dominguez, Miguel Angel
Abstract: Purpose: There is a debate on the role of adjuvant Radiotherapy (RT) in elderly breast cancer patients. The aim is to study Quality of Life (QL) throughout the treatment and follow-up periods in early stages breast cancer patients who have started radiotherapy, and to compare the QL of axillary surgery groups. Methods: 173 patients, ≥65 years completed the EORTC QLQ-C30 and QLQ-BR23, and the Interview for Deterioration in Daily Living Activities in Dementia(IDDD) questionnaires three times throughout treatment and follow-up periods. Linear mixed effect models were used to evaluate longitudinal changes in QL, and whether these changes differed among axillary surgery groups. Results: QL scores were high (>70/100 points) in most QL areas, with moderate limitations (>30) in sexual functioning and enjoyment, future perspective and global QL. In six areas there was a decline at the RT sessions end, that after 6 weeks was recovered. For three areas, there was an improvement in the follow-up measurement compared to the previous assessments. Changes in seven areas were <5 points. Axillary node dissection patients had a body image decrease (6 points) in the follow up period. The lymphadenectomy group had more fatigue (10 points, p = 0.078) than the other two axillary surgery groups. Conclusions: Results orientate towards good patients' adaptation to their disease and treatments, and to administering RT in early stages breast cancer patients. QL differences between the axillary surgery groups and in their evolutions were few but have appeared in key QL areas. Highlights: QL in elderly early stages breast cancer was high along RT and brief follow-up. Limitations were moderate in sexuality areas, future perspective and global QL. There was a decline in QL at the RT sessions end, that was recovered after six weeks. Axillary node dissection patients had a body image decrease in the follow up period. Results orientate towards good patients' adaptation to their disease and treatment.